Synthesis and light scattering study of microgels with interpenetrating polymer networks - Xia, Xiaohu (Langmuir : the ACS journal of surfaces and colloids, 2004)
Monodispersed microgels composed of poly(acrylic acid) (PAAc) and poly(N-isopropylacrylamide) (PNIPAM) interpenetrating polymer networks (IPN) were synthesized by a two-step method, first preparing PNIPAM microgel and then polymerizing acrylic acid that interpenetrates into the PNIPAM network. The growth kinetics of the IPN particle formation was obtained by measuring the turbidity and particle hydrodynamic radius (Rh) as a function of reaction time. IPN and PNIPAM microgels were characterized and compared by dynamic and static light scattering techniques. The concentrated aqueous solutions of the PNIPAM-PAAc IPN microgels exhibit an inverse thermoreversible gelation. In contrast to polymer solutions of poly(NIPAM-co-AAc) that have the inverse thermoreversible gelation, our system can self-assemble into an ordered structure, displaying bright colors. Furthermore, IPN microgels undergo the reversible volume phase transitions in response to both pH and temperature changes associated with PAAc and PNIPAM networks, respectively